Manuscript Legacies and the Contribution of Minangkabau ʿUlamaʾ to the Historiography of Indonesian Islam - Erasiah, Erasiah; Zain, Farid Mat (Jurnal Lektur Keagamaan, 2025)
This article examines the contribution of Minangkabau ʿulamāʾ to the historiography of Islam in the Nusantara. It employs a historiographic approach based on a literature review of primary manuscripts preserved at the Faculty of Adab and Humanities, Imam Bonjol State Islamic University, Padang, as well as dissertations and previous scholarly research on intellectual works by Minangkabau scholars. The study finds, first, that Nusantara ʿulamāʾ manuscripts preserve a wealth of intellectual heritage, offering enduring relevance to the development of Islamic scholarship. Second, these manuscripts exemplify the vitality of the Islamic literary tradition and inspire ongoing commitment to writing as a means of preserving knowledge. Third, Minangkabau ʿulamāʾ manuscripts significantly enrich the historiography of Islam in the archipelago, particularly in providing primary source material that illuminates local historical contexts. Lastly, the presence and substance of these texts challenge orientalist claims that depict Nusantara or Malay Islam as peripheral, instead affirming their integral role within the broader Islamic intellectual tradition.